Hubungan Pengetahuan dengan Tindakan Pencegahan Penyakit Tuberkulosis di Wilayah Kerja Puskesmas Lateri Kota Ambon - Pollan Versilia Wuritimur; Jean Huwae; Heri Jotlely; Ivy V Lawalata (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia, including in the working area of the Lateri Community Health Center in Ambon City. TB transmission occurs through airborne droplets and poses a high risk to family members living in the same household as patients due to frequent and close contact. Family knowledge plays a crucial role in determining preventive behaviors against TB transmission. This study aimed to analyze the relationship between the level of family knowledge and TB prevention practices. This research employed an analytical observational design with a cross-sectional approach. The population and sample consisted of 42 respondents who were family members of TB patients, selected using a total sampling technique. Data were collected through a structured questionnaire and analyzed using the chi-square test with a 95% confidence level (α = 0.05). The results showed that the majority of respondents had good knowledge (81%) and good prevention practices (81%). Bivariate analysis revealed that respondents with poor knowledge tended to have inadequate prevention practices (75%), while those with good knowledge were more likely to demonstrate good prevention practices (79.4%). The statistical test results indicated a p-value of 0.006 (p < 0.05), confirming a significant relationship between knowledge level and TB prevention practices. It can be concluded that higher levels of family knowledge are associated with better TB prevention practices. Therefore, continuous health education is essential to strengthen the role of families in preventing and controlling the transmission of tuberculosis.